Deviant body. The stakes of an identity construction - Mouna, Khalid (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2018)
How does the body build itself as a form of social boundary? This is the central question that this work seeks to study. From the rites of inversion in a ritual ceremony organized every year in the region of Meknès in Morocco, we could observe from our perspective how the body becomes a social issue. A body charged with symbols, which continues to act upon the forms of social exclusion. The purpose of this work is to grasp the empirical character of symbolic body practices, and to account for the variety of forms of its social and cultural uses.